Business Environment Changes and its Influence on Managerial Accountants and Controllers Professional Competence: Empirical Study - Bohumil Král; Libuše Šoljaková (European Financial and Accounting Journal, 2013)
The article describes the outcomes of the project whose purpose is – on the base of “Draft for a common statement” – to state generally accepted requirements for professional competence of managerial accountants and controllers. The important part of the project is empirical research focused on changing requirements on managers and controllers and mapping actual situation in the Czech Republic in this area. The research compares opinions of two groups of respondents – experts who are responsible for professional competence development of controllers on one hand and managers and controllers operating in business environment on the other hand. Paper provides results relating to following areas: general content of the controllers activities, controllers authority and responsibility, requirements for controllers education, professional skills and practical experience, ethical aspects of management accounting as well as quality assurance of the controllers work.
Keywords: M41; 650; Professional Competence; Controller; Management Accountant; Developmental tendencies